Dietary factors and pediatric multiple sclerosis: A case-control study. (July 2018) - Pakpoor, Julia; Seminatore, Brandon; Graves, Jennifer S; Schreiner, Teri; Waldman, Amy T; Lotze, Timothy E; Belman, Anita; Greenberg, Benjamin M; Weinstock-Guttman, Bianca; Aaen, Gregory; Tillema, Jan-Mendelt; McDonald, Jamie C; et al.
Background: The role of diet in multiple sclerosis (MS) is largely uncharacterized, particularly as it pertains to pediatric-onset disease. Objective: To determine the association between dietary factors and MS in children. Methods: Pediatric MS patients and controls were recruited from 16 US centers (MS or clinically isolated syndrome onset before age 18, <4 years from symptom onset and at least 2 silent lesions on magnetic resonance imaging). The validated Block Kids Food Screener questionnaire was administered 2011–2016. Chi-squared test compared categorical variables, Kruskal–Wallis test compared continuous variables, and multivariable logistic regression analysis was performed. Results: In total, 312 cases and 456 controls were included (mean ages 15.1 and 14.4 years). In unadjusted analyses, there was no difference in intake of fats, proteins, carbohydrates, sugars, fruits, or vegetables. Dietary iron was lower in cases ( p = 0.04), and cases were more likely to consume below recommended guidelines of iron (77.2% of cases vs 62.9% of controls, p < 0.001). In multivariable analysis, iron consumption below recommended guidelines was associated with MS (odds ratio = 1.80, p < 0.01). Conclusion: Pediatric MS cases may be less likely to consume sufficient iron compared to controls, and this warrants broader study to characterize a temporal relationship. No other significant difference in intake of most dietary factors was found.